Systemic Lupus Erythematosus in Disguise: Acute Pancreatitis as Initial Presentation - Saeed Abughazaleh MD; Saqr Alsakarneh MD; Mariana Hattar MD; Fouad Jaber MD; Quinton Palmer MD; Hassan Ghoz MD (SAGE Publishing, 2023)
Macrophage activation syndrome (MAS) can rarely coexist with lupus pancreatitis. We report on a 20-year-old woman with abdominal pain, nausea, and vomiting. Laboratories were notable for pancytopenia, elevated liver enzymes, elevated ferritin, lipase, and triglycerides. Chest and abdominal computerized tomography (CT) scans revealed bilateral axillary lymphadenopathy, patchy lower lobe consolidations, small pleural effusions, ascites, and splenomegaly. Peritoneal fluid cytology showed lymphocytes and histiocytes with hemophagocytic changes. Immunological workup met the criteria for systemic lupus erythematosus (SLE). Pulse-dosed steroids relieved her condition. Given the high mortality rate associated with MAS, early detection of concomitant pancreatitis and MAS in the context of underlying SLE is critical.